2013
DOI: 10.1016/j.bbr.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Defeat-induced activation of the ventral medial prefrontal cortex is necessary for resistance to conditioned defeat

Abstract: The ventral medial prefrontal cortex (vmPFC) controls vulnerability to the negative effects of chronic or uncontrollable stress. Dominance status alters responses to social defeat in the conditioned defeat model, which is a model characterized by loss of territorial aggression and increased submissive and defensive behavior following an acute social defeat. We have previously shown that dominant individuals show a reduced conditioned defeat response and increased defeat-induced neural activation in the vmPFC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…In previous studies, we have found that dominant individuals initially respond to social defeat by counter attacking their opponent [4, 36]. Similar to conditioned defeat behavior, the incidence of counter attacking was influenced by the duration of dominance relationship, with 7 day and 14 day dominants showing significantly more counter attacking of resident aggressors than corresponding subordinates and controls.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In previous studies, we have found that dominant individuals initially respond to social defeat by counter attacking their opponent [4, 36]. Similar to conditioned defeat behavior, the incidence of counter attacking was influenced by the duration of dominance relationship, with 7 day and 14 day dominants showing significantly more counter attacking of resident aggressors than corresponding subordinates and controls.…”
Section: Discussionmentioning
confidence: 63%
“…IL lesions prior to environmental enrichment prevent resistance to chronic social defeat, while IL lesions prior to social defeat do not, suggesting that the IL is responsible for the development but not expression of stress resistance. In contrast, pharmacological inactivation of the vmPFC prior to social defeat or uncontrollable tail shock blocks the formation of conditioned defeat and learned helplessness, respectively [18, 36, 42]. Overall, these differences between models suggest that social and physical experiences generate stress resistance via separate cellular and molecular mechanisms in the PL and IL.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that dominant hamsters exhibit a reduced conditioned defeat response compared to subordinates and controls and also exhibit elevated c-Fos expression in the PL and IL cortices (Morrison, et al, 2014; Morrison, et al, 2012). In addition, pharmacological inactivation of the vmPFC during social defeat stress prevents the reduced conditioned defeat response of dominant animals (Morrison, et al, 2013). Altogether, our findings suggest that play deprivation impairs dendritic morphology in the vmPFC and that dysregulated vmPFC neural activity in adulthood may potentiate the effects of social defeat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we use conditioned defeat, a social stress model in Syrian hamsters in which a brief social defeat stress results in a loss of species-typical territorial aggression and an increase in submissive and defensive behavior when animals are later tested with a small, nonaggressive intruder (Huhman et al, 2003; Potegal et al, 1993). We have previously shown that pairs of Syrian hamsters with established dominance relationships respond differently to social defeat stress, such that dominant animals show a reduced conditioned defeat response compared to subordinate counterparts (Morrison et al, 2014; Morrison et al, 2013; Morrison et al, 2012; Morrison et al, 2011). However, hamsters must maintain social dominance for 14 days, and not for 1 or 7 days to exhibit resistance to conditioned defeat (Morrison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%